The Time Bind: When Work Becomes Home and Home Becomes WorkThe Time Bind: When Work Becomes Home and Home Becomes Work, by HochschildArlie Russell. New York: Metropolitan Books, 1997.Finding Time: How Corporations, Individuals, and Families Can Benefit from New Work Practices, by PerlowLeslie. Ithaca, NY: Cornell University Press, 1997. - Leana, Carrie R. (Academy of Management Review, 1998)
The article reviews two books: “The Time Bind: When Work Becomes Home and Home Becomes Work,” by Arlie Russell Hochschild; and “Finding Time: How Corporations, Individuals, and Families Can Benefit from New Work Practices,” by Leslie Perlow.